2010
DOI: 10.1186/1477-3155-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant effect of gold nanoparticles restrains hyperglycemic conditions in diabetic mice

Abstract: BackgroundOxidative stress is imperative for its morbidity towards diabetic complications, where abnormal metabolic milieu as a result of hyperglycemia, leads to the onset of several complications. A biological antioxidant capable of inhibiting oxidative stress mediated diabetic progressions; during hyperglycemia is still the need of the era. The current study was performed to study the effect of biologically synthesized gold nanoparticles (AuNPs) to control the hyperglycemic conditions in streptozotocin induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
216
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(232 citation statements)
references
References 61 publications
8
216
1
Order By: Relevance
“…Furthermore, significantly lower (P#0.05) ROS levels after NP co-incubation compared to cells without NP treatment showed that AuroVist™ NPs are highly biocompatible, most likely due to providing an antioxidative effect. Our findings coincide with previous observations revealing that GNPs can act as an antioxidative agent, by inhibiting the formation of ROS, scavenging free radicals, 47 reasoning that AuroVist™ NPs could exhibit similar effects on cells. Earlier studies revealed that transition metal NPs can be used as antioxidants because of their high reduction potential 48 and thus can also act on an enzymatic level leading to increases in endogenous antioxidant enzymes in streptozotocin-induced diabetic mice.…”
Section: Domey Et Alsupporting
confidence: 82%
“…Furthermore, significantly lower (P#0.05) ROS levels after NP co-incubation compared to cells without NP treatment showed that AuroVist™ NPs are highly biocompatible, most likely due to providing an antioxidative effect. Our findings coincide with previous observations revealing that GNPs can act as an antioxidative agent, by inhibiting the formation of ROS, scavenging free radicals, 47 reasoning that AuroVist™ NPs could exhibit similar effects on cells. Earlier studies revealed that transition metal NPs can be used as antioxidants because of their high reduction potential 48 and thus can also act on an enzymatic level leading to increases in endogenous antioxidant enzymes in streptozotocin-induced diabetic mice.…”
Section: Domey Et Alsupporting
confidence: 82%
“…Previous research work demonstrated the potential toxic effect of GNPs due to their size, surface area, shape, and charge where smaller particles are more toxic than the larger ones [6][7][8] . GNPs demonstrated oxidative stress and macromolecules interaction that could result in histocytotoxicity [9][10][11] . Some research works showed that GNPs with a size of of 5-20 nm were more toxic and had long time accumulation than the larger ones in the vital organs including the kidney [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…AuNP have been used as an anti-inflammatory agent due to AuNP's ability to act as free radical scavengers [17] [18] [19] [21]. Reduction in cellular ROS due to AuNP has been shown to be concentration dependent [22]. Similar to the effects of proliferation and migration, the concentration and size of the nanoparticle affects how the cells interact with the particles [39].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in inflammation may be attributed to anti-oxidative effects of AuNP. Several studies have shown the effectiveness of using AuNP as a free radical scavenger [21] [22]. It was determined that AuNP act as antioxidative agents by inhibiting the formation of ROS and scavenging free radicals, which lowered oxidative stress levels in mice [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation